Revolutionary Theses, Social Reality, and the Tragedy of the Chinese Revolution - Noor, Mansor Mohd (History Department, Semarang State University and Historian Society of Indonesia, 2021)
The Chinese revolutions were the standard-bearers of the world revolution that influenced many independence fighters in colonialized countries. Feudalism, militarism and imperialism were the main ‘enemies’ to the masses that trapped them in the various social inequities of poverty, exploitation and subjugation. Self-worth and national pride were the drivers of the Chinese Revolution as they embedded Chinese nationalism within Marx-Lenin's revolutionary strategy. However, the formation, organization and revolutionary struggle of the Chinese Communist Party was defined and controlled by the Communist International (Comintern) and Stalin that placed them in a straitjacket beyond the border of the Chinese society. A two-stage revolutionary strategy was to be applied in China where the infant CCP must work with Kuomintang (KMT) to gain national liberation of China from imperialism, militarism and feudalism under the leadership of Dr Sun Yat-sen to Chiang Kai-shek. However, defining the changing society in China from afar blinded Stalin interpretation of Marx-Lenin theses as a revolution from below was trigged by the peasant uprisings and KMT’s voices are national revolution but in practice is reactionary. KMT’s voices of revolutionary vigour are to obtain Russian aid and military support but in realpolitik, it massacres the peasants and the labourers who rebel and jeopardies their militarist-capitalist-imperialist agenda. Students of contemporary societal and political change could learn from the Tragedy of the Chinese Revolution, where the body of knowledge applied was socially blinded to the changing social reality of the locality.Revolusi Cina adalah pembawa standar revolusi dunia yang mempengaruhi banyak pejuang kemerdekaan di negara-negara terjajah. Feodalisme, militerisme, dan imperialisme adalah 'musuh' utama massa yang menjebak mereka dalam berbagai ketidakadilan sosial berupa kemiskinan, eksploitasi dan penaklukan. Hal ini mendorong terjadinya revolusi. Harga diri dan kebanggaan nasional adalah pendorong Revolusi Cina karena mereka menanamkan nasionalisme Cina dalam strategi revolusioner Marx-Lenin. Namun, pembentukan, organisasi dan perjuangan revolusioner Partai Komunis Tiongkok ditentukan dan dikendalikan oleh Komunis Internasional (Komintern) dan Stalin yang menempatkan mereka dalam jaket pengekang di luar batas masyarakat Tiongkok. Strategi revolusioner dua tahap akan diterapkan di Tiongkok di mana PKC yang masih bayi harus bekerja dengan Kuomintang (KMT) untuk mendapatkan pembebasan nasional Tiongkok dari imperialisme, militerisme, dan feodalisme di bawah kepemimpinan Dr Sun Yat-sen ke Chiang Kai-shek. Namun, mendefinisikan masyarakat yang berubah di Cina dari interpretasi Stalin yang membutakan atas tesis Marx-Lenin sebagai revolusi dari bawah dipicu oleh pemberontakan petani dan suara KMT adalah revolusi nasional tetapi dalam praktiknya adalah reaksioner. Suara kekuatan revolusioner KMT adalah untuk mendapatkan bantuan dan dukungan militer Rusia tetapi dalam politik nyata, KMT membantai para petani dan buruh yang memberontak dan membahayakan agenda militeris-kapitalis-imperialis mereka. Mahasiswa perubahan sosial dan politik kontemporer dapat belajar dari Tragedi Revolusi Cina, di mana tubuh pengetahuan yang diterapkan secara sosial dibutakan oleh realitas sosial yang berubah dari lokalitas.